Supportive communication climate in the self-development of Generation Z - Dwi Purbaningrum; Rini Sudarmanti (Bricolage : Jurnal Magister Ilmu Komunikasi, 2022)
Generation-Z has become a popular topic in mass media, due to their development amidst the growing online lifestyle of our society. Born between 1996-2010, the internet has become part of their development, as it slowly grew into our society. Generation-Z are the true digital native. They have grown accustomed to using their handphone all day long, doing various activities with it. Such custom is enhanced by the Covid-19 pandemic which reduced, significantly, the possibility of a direct physical contact with other members of the society since March 2020. The contact also includes their learning and working process—where schools and offices alike were forced to take their operations online. This research used the qualitative-descriptive approach to get a natural depiction of the informants, and a study case to get a holistic data from the respondents, a group of Generation-Z. The purpose of this research is to find out how Generation-Z interprets the online learning situation. Using Modern Theories of Learning and symbolic interactionism, it was found that informants grew up in a supportive communication climate while learning from home. Informants are also more productive as they could study while working, interning in several places. This finding concluded that Gen-Z could use their online situation to develop themselves.